2017
DOI: 10.1002/etc.3683
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pharmaceuticals on a unionid mussel (Lampsilis siliquoidea): An examination of acute and chronic endpoints of toxicity across life stages

Abstract: The toxicity and bioconcentration of 3 pharmaceuticals (amitriptyline, iopamidol, and sertraline) were examined using multiple life stages (larval, juvenile, and adult) of the unionid mussel Lampsilis siliquoidea. The endpoints examined varied with life stage but included survival, behavior (algal clearance rate, filtering frequency), and oxidative stress. Iopamidol was not toxic at concentrations up to 101 mg/L. Sertraline was the most toxic chemical (50% lethal concentrations [LC50] and effect concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…CI was widely used as an indicator of the physiological status of the mollusks (Luna-Acosta et al, 2017;Tejeda-Vera et al, 2007). In addition, CR and RR represent key parameters in the physiology of suspension-feeding bivalves and are mostly likely to reflect toxic effects caused by environmental perturbations (Li et al, 2002;Echevarria et al, 2012;Chandurvelan et al, 2012;Gilroy et al, 2016;Hu et al, 2017;Sui et al, 2016;Xu et al, 2016;Basti et al, 2016;Ong et al, 2017). Reactive oxygen species (ROS) could be generated in marine organism under stressful environmental conditions, and excessive ROS production could lead to oxidative stress, causing damage to tissues and cellular components in marine organisms (V Valavanidis et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…CI was widely used as an indicator of the physiological status of the mollusks (Luna-Acosta et al, 2017;Tejeda-Vera et al, 2007). In addition, CR and RR represent key parameters in the physiology of suspension-feeding bivalves and are mostly likely to reflect toxic effects caused by environmental perturbations (Li et al, 2002;Echevarria et al, 2012;Chandurvelan et al, 2012;Gilroy et al, 2016;Hu et al, 2017;Sui et al, 2016;Xu et al, 2016;Basti et al, 2016;Ong et al, 2017). Reactive oxygen species (ROS) could be generated in marine organism under stressful environmental conditions, and excessive ROS production could lead to oxidative stress, causing damage to tissues and cellular components in marine organisms (V Valavanidis et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are far fewer studies on the sensitivities of freshwater mussels to PPCPs than to inorganic contaminants, the limited studies indicate that for some PPCPs, mussels are more sensitive than other aquatic organisms, while for other PPCPs, the sensitivity is comparable. Gilroy et al ( 2017 ) reported LC50s of 0.3 and 0.4 mg/L for the SSRI amitriptyline in a 24-h test with glochidia and a 14-day test with juvenile L. siliquoidea , respectively, as well as a 24-h LC50 of 0.06 mg/L for glochidia and a 28-day LC50 of 0.04 mg/L for juvenile L. siliquoidea for sertraline. In comparison, Minguez et al ( 2014 ) reported 48-h D. magna EC50s of 4.8 mg/L for amitriptyline, and 1.2 mg/L for sertraline, suggesting a difference in sensitivity of at least an order of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mussels are suitable to be fed by sea anemones in home aquariums [ 102 ]. However, bivalves can close their valves for prolonged periods of time under adverse environmental condition [ 103 , 104 ]. In other words, how can sea anemones obtain nourishments from mussels, if these bivalves tightly close the valves when feel the predator attack?…”
Section: Resultsmentioning
confidence: 99%